Combining Chalk Talk with PowerPoint to Increase In-class Student Engagement - Swati Betharia (University of Minnesota Libraries Publishing, 2016)
In striving to attain a higher degree of in-class student engagement, and target a larger number of preferred student-learning styles, this case study describes a multimodal teaching approach. PowerPoint slides have gradually gained popularity over the more traditional chalk and talk lecture design. The student population in today's age seeks more non-passive modes of information delivery. Numerous novel approaches to enhance active learning, such as flipped classroom and problem-based learning, have recently been explored. While working well for therapeutic and lab-based courses, these formats may not be best-suited for all basic science topics. The importance of basic science in a pharmacy curriculum is well emphasized in the 2016 ACPE Standards. To actively involve students in a pharmacology lecture on diuretics, a session was designed to combine the PowerPoint and chalk talk approaches. Students created 10 concept diagrams following an instructor, who explained each step in the process using a document camera. For visual learners, these diagrams provided a layered representation of the information, gradually increasing in complexity. For learners with a preference for the reading learning style, the information was also available in corresponding PowerPoint slides. Scores from pre- and post-session quizzes indicated a high level of concept understanding and recall (median 1 [IQR 0 - 2] vs 4 [IQR 3 - 5]; p<0.001). The student perception survey data reported higher in-class attention levels (76%), an appreciation for the utility of self-created concept diagrams (88%), and a call for additional sessions being presented in this format (73%). Targeting a variety of student learning styles by using the active development of concept diagrams, in addition to traditional PowerPoint slides, can promote student engagement and enhance content understanding.   Type: Case Study